2019
DOI: 10.1002/biof.1516
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal plants in traumatic brain injury: Neuroprotective mechanisms revisited

Abstract: Traumatic brain injury (TBI) is the most prevalent health problem affecting all age groups, and leads to many secondary problems in other organs especially kidneys, gastrointestinal tract, and heart function. In this review, the search terms were TBI, fluid percussion injury, cold injury, weight drop impact acceleration injury, lateral fluid percussion, cortical impact injury, and blast injury. Studies with Actaea racemosa, Artemisia annua, Aframomum melegueta, Carthamus tinctorius, Cinnamomum zeylanicum, Croc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 172 publications
(300 reference statements)
1
11
0
Order By: Relevance
“…sylvestris may reduce xerostomia through increasing the salivary secretion or maintaining the mucosal water content in oral cavity. The reduction of cisplatin-induced renal and hepatic side effects has also been demonstrated in rats (n = 56; male rats of 9-to 11-weeks old) Indeed, M. sylvestris significantly reduced neuronal injury by mechanisms involving raise in superoxide dismutase and CAT activities, suppression of nuclear factor kappa B, IL-1 and IL-6, and glial fibrillary acidic protein expression confirming its neuroprotective effects on central nervous system (Keshavarzi et al, 2019). The role of the aqueous extract from M. sylvestris aerial parts was assessed in rat models with induced inflammation (Sleiman & Daher, 2009).…”
Section: Anticancer Activities Of Malva Plantsmentioning
confidence: 59%
See 1 more Smart Citation
“…sylvestris may reduce xerostomia through increasing the salivary secretion or maintaining the mucosal water content in oral cavity. The reduction of cisplatin-induced renal and hepatic side effects has also been demonstrated in rats (n = 56; male rats of 9-to 11-weeks old) Indeed, M. sylvestris significantly reduced neuronal injury by mechanisms involving raise in superoxide dismutase and CAT activities, suppression of nuclear factor kappa B, IL-1 and IL-6, and glial fibrillary acidic protein expression confirming its neuroprotective effects on central nervous system (Keshavarzi et al, 2019). The role of the aqueous extract from M. sylvestris aerial parts was assessed in rat models with induced inflammation (Sleiman & Daher, 2009).…”
Section: Anticancer Activities Of Malva Plantsmentioning
confidence: 59%
“…This suggests that M. parviflora can be effectively used to prevent or delay Alzheimer's disease progression (Medrano‐Jimenez et al, ). Indeed, M. sylvestris significantly reduced neuronal injury by mechanisms involving raise in superoxide dismutase and CAT activities, suppression of nuclear factor kappa B, IL‐1 and IL‐6, and glial fibrillary acidic protein expression confirming its neuroprotective effects on central nervous system (Keshavarzi et al, ). The role of the aqueous extract from M. sylvestris aerial parts was assessed in rat models with induced inflammation (Sleiman & Daher, ).…”
Section: Pharmacological Properties Of Malva Plantsmentioning
confidence: 88%
“…Results showed this effect by decreased oxidative stress and cerebral edema, rise in BDNF level, protection of synaptic proteins and mitochondria, and microglial activation. Also, it has been shown that it can decrease in IL-6, TNF-α, IL-1β, and MCP-1 and improve toll-like receptor 4 and aquaporin-4 expression [114]. Additionally, the activation of the Nrf2 pathway is one of the most important mechanisms regarding this action [115].…”
Section: Neuroprotective Effectsmentioning
confidence: 99%
“…Many studies have tried to explain the mechanism through which HM functions in TBI, showing that HM decreases neuronal injury by increasing superoxide dismutase and catalase activities, as well as by suppressing the expression of interleukin (IL)-1, IL-6, nuclear factor kappa B, and glial fibrillary acidic protein ( 88 ). Another study showed that HM protected a rat model of TBI, possibly via immune-promoting, anti-inflammatory, and neuroprotective effects ( 89 ).…”
Section: Discussionmentioning
confidence: 99%